قياس بعض السمات الشخصية لدى أساتذة التربية البدنية والرياضية - غندير, نور الدين; نصير, أحميدة; جرمون, علي (جامعة الوادي - University of Eloued, 2020)
هدفت الدراسة الحالية إلى قياس بعض السمات الشخصية لدى أساتذة التربية البدنية والرياضية وعلاقتها بدافعية التعلم نحو درس التربية البدنية والرياضية لدى تلاميذ المرحلة الثانوية بمدينة تقرت، وكذا تحديد الفروق في دافعية التعلم نحو درس التربية البدنية والرياضية تبعا لمتغير جنس التلميذ، وتكونت عينة الدراسة من 23 أستاذ و310 تلميذ اختيروا بطريقة عشوائية بسيطة، واعتمدت الدراسة على استبانة السمات الشخصية واستبانة دافعية التعلم نحو درس التربية البدنية والرياضية، وأظهرت النتائج أن مستوى بعض السمات الشخصية لدى أساتذة التربية البدنية والرياضية مرتفع، ومستوى دافعية التعلم نحو درس التربية البدنية والرياضية لدى التلاميذ مرتفع، وتوجد فروق في دافعية التعلم نحو درس التربية البدنية والرياضية لدى التلاميذ تعزى لمتغير الجنس، ولا توجد علاقة بين مستوى بعض السمات الشخصية لأستاذ التربية البدنية والرياضية ودافعية التعلم نحو درس التربية البدنية والرياضية لدى التلاميذ.Abstract: The study aimed to measuring some personality traits of physical education and sports teachers and its relationship to learning motivation in secondary-schools in the tougourt city, and determination the differences in learning motivation due to the gender, the study sample consisted of (23) teachers and (310) pupils, They were randomly selected, the researchers used the descriptive approach, A personality traits questionnaire was used and learning motivation, the findings show that a high level of teachers personality traits and pupils learning motivation, The results also showed there is a difference in learning motivation to sports physical education lesson due to gender variable, and while there is no relationship between personality traits level and learning motivation of pupils in secondary-schools.
مقال
Keywords: سمات شخصية ; دافعية تعلم ; أستاذ تربية بدنية ورياضية; personality traits; learning motivation; physical education and sports teachers; pupils of secondary-schools